2009
DOI: 10.1177/0170840609334951
|View full text |Cite
|
Sign up to set email alerts
|

Merging, Masquerading and Morphing: Metaphors and the World Wide Web

Abstract: We examine the role of metaphors in relation to Web-based phenomena through a comparative study of 29 Web portals, established under a World Bank project known as the Development Gateway. Our analysis suggests that three metaphors -expert, market and community -are particularly significant across these portals, either separately or in combination. The study indicates three particular ways in which these metaphors can combinemerging, masquerading and morphing. We conclude by discussing the implications of using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…For example, we found that a discussion forum feature, which some have equated with subjectivist and participative forms of knowledge, was often a convergence of many elements: words, visuals, rules, roles assigned to parties, and these elements could send out different signals. We found cases of discussion fora wherein words and headings were welcoming and inclusive, yet rules and roles were so restrictive and confining that only one expert participant could give input, and all other participants were restricted to "silent" reading [26]. Cases such as these would call into question the assumption that interactive mechanisms like a "discussion forum" or "chat" can automatically be equated with participative forms of knowledge.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, we found that a discussion forum feature, which some have equated with subjectivist and participative forms of knowledge, was often a convergence of many elements: words, visuals, rules, roles assigned to parties, and these elements could send out different signals. We found cases of discussion fora wherein words and headings were welcoming and inclusive, yet rules and roles were so restrictive and confining that only one expert participant could give input, and all other participants were restricted to "silent" reading [26]. Cases such as these would call into question the assumption that interactive mechanisms like a "discussion forum" or "chat" can automatically be equated with participative forms of knowledge.…”
Section: Methodsmentioning
confidence: 91%
“…Part of this emancipation involves large numbers of "ordinary" people around the world who can now participate electronically in the production of knowledge that affects their lives. Under this view of technology, it has been argued that the Internet has undoubtedly facilitated the collective production of knowledge [26] as, perhaps, best exemplified by Wikipedia -a rapidly growing, collaborative website fuelled by the contributions of some millions of people around the world. Such a view of collective knowledge production is consistent with what has been called "subjectivist" perspectives of knowledge, which emphasize the participatory, constructionist processes whereby knowledge is generated using a bottom-up approach, thus suggesting a decoupling of knowledge from the strictures of control.…”
Section: Introductionmentioning
confidence: 99%
“…Criticism of traditional website design has been that 'in mimicking paper forms of communication, the user under-utilizes the power of the new electronic medium' (Dillon andGushrowski 2000, in Coupland andBrown, 2004), while Chaudhri and Wang (2007:242) in their study of the role of websites in CSR reporting in India noted a 'lack of creativity' in exploiting multimedia and interactivity in supporting corporate messages. However, although the traditional website genre, containing mainly a mixture of text and photos and other images, is still quite prevalent, corporate websites are becoming increasingly sophisticated, containing videos, podcasts, blogs and fora and so are becoming more interactive and as such boundaries between corporate and public more blurred (see Coupland and Brown, 2004, Pablo and Hardy, 2009, Leonard 2013. In this section we identify from the existing literature five emergent elements which, we argue, could constitute an initial framework for conceptualising Corporate Web Identity' (CWI).…”
Section: Towards An Understanding Of Emergent Corporate Web Identitymentioning
confidence: 99%
“…Yet for many of its potential stakeholders the first encounter with an organization is through its webpages (Coupland and Brown, 2004;Pablo and Hardy, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation